K05 Genetic Discrimination and Predictive Testing for Huntington's Disease and Familial Cancer in Northern Scotland: The I-Respond-UK Study. (17th September 2014) - Wedderburn, S; Rae, D; Williams, J; Carey-Heaton, R; Miedzybrodzka, Z
Abstract : Background: In predictive testing for HD and familial cancer, potential genetic discrimination is commonly discussed. It is over ten years since experiences of insurance and discrimination issues have been documented in the UK. The insurance industry entered into a voluntary moratorium on use of genetic test information. The i-RESPOND-HD Study reported perceptions, experiences and responses to genetic discrimination of those at risk of HD in the USA, Canada and Australia. Aim: To assess current experiences of genetic discrimination in the UK to inform predictive testing counselling. Methods: The i-RESPOND HD postal questionnaire was adapted for the UK, and for familial cancer. Questionnaires were sent to 131 from North Scotland. Results: 43 individuals responded. 55% positive for the HD gene; 19% for a cancer gene. None reported specific discrimination events. Both those at risk of HD (72%) and cancer (34%) reported they would actively avoid insurance discrimination. 55% and 23% respectively reported that they would actively avoid employment and other forms of genetic discrimination. The majority were unaware of current relevant laws. Only 9% of at risk HD and 3.2% of those at risk of cancer had sought external advice on genetic discrimination. Conclusions: In the UK, those at risk of HD and familial cancer actively seek to avoid genetic discrimination in insurance and elsewhere, but actual discrimination is uncommon. In contrast in the 2010 i-RESPOND HD Study in US, Canada and Australia genetic discrimination was reported by 26% in insurance domains and 33% in relationships.